MICROSCOPICALLY PROPERTIES OF PLASMA WITH CONDUCTIVE MACROPARTICLES - Baimbetov, F.; Davletov, A.E.; Mukhametkarimov, Ye.S.; Kudyshev, Zh.A. (Recent Contributions to Physics, 2011)
On the basis of the Bogolyubov chain of equations pseudopotential model of particle interaction in dusty plasmas is proposed. In the absence of surrounding particles, the base interaction potentials of dust particles with charged particles (electrons, ions) and with each other are calculated by the method of electric images, dust particles are supposed charged conducting spheres. Investigated are the radial distribution functions and static structure factors. The results obtained adequately describe the possibility of short- and long-range order formations.